Conditional testing of multiple variants associated with bone mineral density in the FLNB gene region suggests that they represent a single association signal - Mullin, B.; Mamotte, Cyril; Prince, R.; Spector, T.; Dudbridge, F.; Wilson, S. (PubMed, 2013)
Background: Low bone mineral density (BMD) is a primary risk factor for osteoporosis and is a highly heritable trait, but appears to be influenced by many genes. Genome-wide linkage studies have highlighted the chromosomal region 3p14-p22 as a quantitative trait locus for BMD (LOD 1.1 - 3.5). The FLNB gene, which is thought to have a role in cytoskeletal actin dynamics, is located within this chromosomal region and presents as a strong candidate for BMD regulation. We have previously identified significant associations between four SNPs in the FLNB gene and BMD in women. We have also previously identified associations between five SNPs located 5' of the transcription start site (TSS) and in intron 1 of the FLNB gene and expression of FLNB mRNA in osteoblasts in vitro. The latter five SNPs were genotyped in this study to test for association with BMD parameters in a family-based population of 769 Caucasian women. Results: Using FBAT, significant associations were seen for femoral neck BMD Z-score with the SNPs rs11720285, rs11130605 and rs9809315 (P = 0.004 – 0.043). These three SNPs were also found to be significantly associated with total hip BMD Z-score (P = 0.014 – 0.026). We then combined the genotype data for these three SNPs with the four SNPs we previously identified as associated with BMD and performed a conditional analysis to determine whether they represent multiple independent associations with BMD. The results from this analysis suggested that these variants represent a single association signal. Conclusions: The SNPs identified in our studies as associated with BMD appear to be part of a single association signal between the FLNB gene and BMD in our data. FLNB is one of several genes located in 3p14-p22 that has been identified as significantly associated with BMD in Caucasian women.